OPTIMIZING BUSINESS ENGLISH TEACHING TO UNIVERSITY STUDENTS: INSIGHTS AND RECOMMENDATIONS - Nurdiana, Nurdiana (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
English is a compulsory subject at schools and universities in Indonesia, with students commonly learning General English and English for Academic Purposes. Some universities integrate Business English or English for Specific Purposes into their curriculum, given the increasing demand for workplace communication skills. However, teaching Business English requires not only linguistic competence but also familiarity with professional contexts, appropriate instructional strategies, and mastery of specialized terminology. This study aimed to discuss insights and recommendations for teaching Business English to university students by conducting a systematic literature review. This issue warrants further exploration as evidence shows that many Indonesians learning Business English struggle to perform key business communication tasks, such as negotiating, giving presentations, and writing emails and reports, due to limited exposure to real-world language use and insufficient instructional support. The study concludes that Business English teaching can be enhanced through the integration of simulations and role-plays, as well as the use of authentic materials that reflect actual workplace practices. These approaches help bridge the gap between classroom learning and real business communication demands. Key Words : Business English; role-plays; authentic materials; university students